2019
DOI: 10.1097/dss.0000000000001641
|View full text |Cite
|
Sign up to set email alerts
|

Laser Ablation of the Recipient Area With Platelet-Rich Plasma–Enriched Epidermal Suspension Transplant in Vitiligo Surgery: A Pilot Study

Abstract: This study indicates that PRP-enriched epidermal suspension transplant (LA-PEEST) has the potential to improve the rate of healing and repigmentation in vitiligo patches. Further investigations and larger controlled trials are required to establish this technique as a rapid surgical method to restore pigmentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 13 publications
5
35
2
Order By: Relevance
“…Specifically, six clinical studies regarding the use of PRP in vitiligo have been identified, with a total of 253 patients. 1,[12][13][14][15][16] The mean time of follow-up of treated patients was 6 months (ranging between 3 and 12 months). 1,[12][13][14][15][16] In all reports, 1,[12][13][14][15][16] all treated patients showed a stable vitiligo, and a significantly higher improvement in the PRP groups was always observed compared to control groups, regardless of the combined treatment associated with PRP.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, six clinical studies regarding the use of PRP in vitiligo have been identified, with a total of 253 patients. 1,[12][13][14][15][16] The mean time of follow-up of treated patients was 6 months (ranging between 3 and 12 months). 1,[12][13][14][15][16] In all reports, 1,[12][13][14][15][16] all treated patients showed a stable vitiligo, and a significantly higher improvement in the PRP groups was always observed compared to control groups, regardless of the combined treatment associated with PRP.…”
Section: Resultsmentioning
confidence: 99%
“…1,[12][13][14][15][16] The mean time of follow-up of treated patients was 6 months (ranging between 3 and 12 months). 1,[12][13][14][15][16] In all reports, 1,[12][13][14][15][16] all treated patients showed a stable vitiligo, and a significantly higher improvement in the PRP groups was always observed compared to control groups, regardless of the combined treatment associated with PRP. 1,[12][13][14][15][16] Regarding the side effects, PRP in vitiligo patients is safe, without important and specific side effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the progressive loss of functional melanocytes associated with an inflammatory/autoimmune context and the failure to spontaneously recover skin functionality, it has been proposed to consider vitiligo as a degenerative disease . In addition to pharmacological treatment, several different surgical and regenerative approaches have been proposed to restore pigmentation in vitiligo including dermabrasion, epidermal or hair follicle outer root sheath cell suspension transplant, cultured epithelial cells or cultured epithelia sheet graft, minipunch graf, suction blistering grafting, platelet‐rich plasma‐enriched (PRP) supplementation and the use of autologous mesenchymal stem cells (MSCs) . Repigmentation through dermis stimulation reflects the emerging key role of the dermal compartment in vitiligo since dermoabrasion and mechanical needling deeply stimulate the dermis and induce processes similar to a wound‐healing response with the release of different growth factors and inflammatory mediators .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, clinical studies demonstrated that PRP injection significantly improves the clinical outcome when used in combination with fractional CO 2 laser treatment, or when associated with term NB‐UVB phototherapy, whereas PRP injection alone achieves unsatisfactory results . Similarly, a very recent study proposed the usage of PRP as supplementation of epidermal cell suspension, since graft‐based surgical methods to restore melanocyte abundance demonstrated mixed results in generating cosmetically acceptable repigmentation and need improvement. In particular, the preoperative care and postoperative care of the recipient site are crucial to obtain maximum adherence and to maintain survival of transplanted melanocytes.…”
Section: Introductionmentioning
confidence: 99%